A Process Study on Thinning of Arctic Winter Cirrus Clouds With High‐Resolution ICON‐ART Simulations. Issue 11 (5th June 2019) - Gruber, Simon; Blahak, Ulrich; Haenel, Florian; Kottmeier, Christoph; Leisner, Thomas; Muskatel, Harel; Storelvmo, Trude; Vogel, Bernhard
Abstract: In this study, cloud‐resolving simulations of a case study for a limited area of the hibernal Arctic were performed with the atmospheric modeling system ICON‐ART (ICOsahedral Nonhydrostatic‐Aerosol and Reactive Trace gases). A thorough comparison with data both from satellite as well as aircraft measurement is presented to validate the simulations. In addition, the model is applied to clarify the microphysical processes occurring when introducing artificial aerosol particles into the upper troposphere with the aim of modifying cirrus clouds in the framework of climate engineering. Former modeling studies investigating the climate effect of this method were performed with simplifying assumptions and much coarser resolution, reaching partly contradicting conclusions concerning the method's effectiveness. The primary effect of seeding is found to be a reduction of ice crystal number concentrations in cirrus clouds, leading to increased outgoing longwave radiative fluxes at the top of the atmosphere, thereby creating a cooling effect. Furthermore, a secondary effect is found, as ice crystals formed from the injected seeding aerosol particles lead to enhanced riming of cloud droplets within the planetary boundary layer. This effectively reduces the coverage of mixed‐phase clouds, thus generating additional cooling by increased upward longwave radiative fluxes at the surface. The efficacy of seeding cirrus clouds proves to be relatively independent from the atmospheric background conditions, scales with the number concentrations of seeding particles, and is highest for large aerosol particles. Key Points: A first high‐resolution process study of cirrus cloud seeding using ICON‐ART is presented A strong decrease of ice crystal number concentration in cirrus clouds is found due to seeding The effect of seeding is amplified due to a reduction of mixed‐phase cloud cover